2011
DOI: 10.1016/j.juro.2010.10.068
|View full text |Cite
|
Sign up to set email alerts
|

Renal Oncocytosis: Management and Clinical Outcomes

Abstract: Purpose Renal oncocytosis is an extremely rare pathological condition in which renal parenchyma is diffusely involved by numerous oncocytic nodules, in addition to showing a spectrum of other oncocytic changes. Our aim was to describe our experience with renal oncocytosis, focusing on management and outcomes. Materials and Methods Twenty patients with a final pathologic diagnosis of renal oncocytosis from July 1995 through June 2009 were included in the analysis. Patient demographics, intraoperative variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…However, 4-6% will have multifocal disease while 4% will have bilateral disease (4). Patients range in age from 10 to 94 years of age (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), with most occurring in the seventh decade of life. Our 12 year old patient is one of the younger ones described to date.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, 4-6% will have multifocal disease while 4% will have bilateral disease (4). Patients range in age from 10 to 94 years of age (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), with most occurring in the seventh decade of life. Our 12 year old patient is one of the younger ones described to date.…”
Section: Discussionmentioning
confidence: 99%
“…Renal oncocytoma has traditionally been regarded as a benign neoplastic tumor; however, chromophobe renal cell carcinoma has been described within the same kidney (1,8,11). If possible, nephron sparing surgery should be undertaken.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Renal oncocytosis was first described in 1982 (Warfel and Eble 1982): multiple and bilateral oncocytic nodules and a spectrum of oncocytic changes are found diffusely throughout the renal parenchyma. A large series investigating renal oncocytosis revealed that hybrid development of RO and chRCC was most common (Adamy et al 2011). Hybrid oncocytic chromophobe tumours are tumours which display histological features of both chRCC and RO.…”
Section: Epidemiologymentioning
confidence: 99%